Noninvasive Diagnostic Technique in Stenotic Coronary Atherosclerosis - A. Yu. Vasilyev; N. N. Mikheyev; T. P. Makarova (Общая реаниматология)
Objective: to determine the sensitivity and specificity of combined stress echocardiography (EchoCG) using dipyri-damole and dobutamine in diagnosing and defining the extent of stenotic coronary lesions in coronary heart disease (CHD) in a group of critically ill patients who are unable to perform a physical exercise.Materials and methods: the study included 57 male patients with suspected acute coronary syndrome who underwent stress EchoCG using dipyridamole in high doses in combination with dobutamine, as well as coronary angiography.Results: stress EchoCG could bring up to the diagnostic criteria in all the patients, of whom 9 patients were found at coronary angiography to have no coronary lesion, 34 and 14 patients had one- and many-vessel lesions, respectively. The sensitivity and specificity of combined stress EchoCG were significantly higher than those of EchoCG used in the diagnosis of CHD.Conclusion: stress EchoCG using dipyridamole in combination with dobutamine is a highly informative safe noninvasive technique for diagnosing CHD, its helps to identify patients with atypical acute coronary syndrome and to form a group of patients to be subject to urgent coronarography and angiosurgical intervention. The pattern of segmental contractile disorders at the height of exercise during combined stress Echo-CG makes it possible to define the site of stenotic coronary atherosclerosis with 97.3% sensitivity and to diagnose many-vessel lesion with 100% sensitivity and 100%specificity.